Identification, Assessment and Mitigation of Environment Side Risks for Malaysian Manufacturing - Shahbaz, M. S.; Kazi, A. G.; Othman, B.; Javaid, M.; Hussain, K.; Rasi, R. Z. R. M. (Engineering, Technology & Applied Science Research, 2019)
Malaysia has faced many supply chain issues that not only have affected enterprises but also the overall economy. Natural disasters that badly affect the performance of Malaysian enterprises strongly demand a comprehensive investigation of supply chain risks. Effective mitigation strategy can only be operationalized when risks are appropriately identified and assessed. Supply chain collaboration has been verified to have a positive impact on the performance but only a limited number of studies investigate it as a risk mitigation tool. The current study presents a guiding framework for identification, assessment, and migration of environment side risks for Malaysian manufacturing. A questionnaire has been developed and distributed by systemic probability sampling. Data have been collected from the Federation of Manufacturing Malaysia through an online survey. The data were purified from missing values and outliers and were analyzed through structural equational modeling through Smart PLS. A total of nine environment side risks were identified. In risk assessment, it has been found that an environment side risk has negative effects on supply chain performance. While these risks can be mitigated through supply chain collaboration, they cannot be mitigated completely. This study will help managers to understand how environment side risks are affecting enterprise performance and how they can avoid these risks. This study covers only environment side risks while future research can be on operational risks and various other approaches that can be proposed for mitigation.